Relationship Between ABCB1 Polymorphisms and Cold Pain Sensitivity Among Healthy Opioid-naive Malay Males - Zahari, Z.; Lee, C.S.; Ibrahim, M.A.; Musa, N.; Mohd Yasin, M.A.; Lee, Y.Y.; Tan, S.C.; Mohamad, N.; Ismail, R. (Blackwell Publishing, 2017)
Background: Endogenous and exogenous opioids are substrates of the permeability glycoprotein (P-gp) efflux transporter, which is encoded by the ABCB1 (MDR1) gene. Genetic polymorphisms of ABCB1 may contribute to interindividual differences in pain modulation and analgesic responses. We investigated the relationship between ABCB1 polymorphisms and cold pain sensitivity among healthy males. Methods: Cold pain responses, including pain threshold and pain tolerance, were measured using the cold-pressor test (CPT). DNA was extracted from whole blood and genotyped for ABCB1 polymorphisms, including c.1236C>T (rs1128503), c.2677G>T/A (rs2032582), and c.3435C>T (rs1045642), using the allelic discrimination real-time polymerase chain reaction. Results: A total of 152 participants were recruited in this observational study. Frequencies of mutated allele for c.1236C>T, c.2677G>T/A, and c.3435C>T polymorphisms were 56.6%, 49.7%, and 43.4%, respectively. Our results revealed an association of the CGC/CGC diplotype (c.1236C>T, c.2677G>T/A, and c.3435C>T) with cold pain sensitivity. Participants with the CGC/CGC diplotype had 90% and 72% higher cold pain thresholds (87.62 seconds vs. 46.19 seconds, P = 0.010) and cold pain tolerances (97.24 seconds vs. 56.54 seconds, P = 0.021), respectively, when compared with those without the diplotype. Conclusion: The CGC/CGC diplotype of ABCB1 polymorphisms was associated with variability in cold pain threshold and pain tolerance in healthy males.